Prognostic Impact of Tumor Size on Pancreatic Neuroendocrine Tumor Recurrence May Have Racial Variance. Issue 3 (March 2021) - Zheng-Pywell, Rui; Fang, Amanda; AlKashash, Ahmad; Awad, Seifeldin; Reddy, Sushanth; Vickers, Selwyn; Heslin, Martin; Dudeja, Vikas; Chen, Herbert; Rose, John Bart
Abstract : Objective: The incidence of pancreatic neuroendocrine tumors (PNETs) has increased over the last decade. Black patients have worse survival outcomes. This study investigates whether oncologic outcomes are racially disparate at a single institution. Methods: Retrospective analysis was performed on 151 patients with resected PNETs between 2010 and 2019. Results: More White males and Black females presented with PNETs ( P = 0.02). White patients were older (65 years vs 60 years; P = 0.03), more likely to be married ( P < 0.01), and had higher median estimated yearly incomes (28, 973 vs 17, 767; P < 0.01) than Black patients. Overall and disease-free survival were not different. Black patients had larger median tumor sizes (30 mm vs 23 mm; P = 0.02). Tumor size was predictive of recurrence only for White patients (hazard ratio, 1.02; P = 0.01). Collectively, tumors greater than 20 mm in size were more likely to have recurrence ( P = 0.048), but this cutoff was not predictive in either racial cohort independently. Conclusions: Black patients undergoing curative resection of PNETs at our institution presented with larger tumors, but that increased size is not predictive of disease-free survival in this population.